Parent Socialization of Coping and Child Emotion Regulation Abilities: A Longitudinal Examination. Issue 4 (29th November 2019) - Peisch, Virginia; Dale, Chelsea; Parent, Justin; Burt, Keith
Abstract : This study examined the hypothesis that parent socialization of coping (SOC) would have a longitudinal relation with child emotion regulation abilities. Participants included a sample of 256 parents of 5‐ to 12‐year‐old children (child M age = 8.36, SD  = 2.03, 54.7% male; parent M age = 34.49, SD  = 6.20, 59% female). Data on demographic information, parenting behaviors, and child emotion regulation abilities were collected via online questionnaires at baseline and 12 months. Results from longitudinal structural equation modeling (SEM) analyses suggested that parent SOC, measured at baseline, predicted child adaptive and maladaptive emotion regulation, measured 12 months later. More specifically, parental engagement coping suggestions predicted child's adaptive emotion regulation, whereas parental disengagement coping suggestions predicted child's maladaptive emotion regulation. Further, child gender emerged as a moderator in the longitudinal association between socialization of engagement coping and child adaptive emotion regulation: Whereas this association was small and marginally significant for girls, it was large and statistically significant for boys. Results highlight the importance of parent SOC as potentially contributing to emotion regulation abilities of 5‐ to 12‐year‐olds. Abstract : Este estudio examinó la hipótesis de que la socialización del afrontamiento por parte de los padres tendría una relación longitudinal con las habilidades de regulación emocional de los niños. Los participantes fueron una muestra de 256 padres de niños de entre 5 y 12 años (edad promedio de los niños = 8.36, desviación típica = 2.03, el 54.7 % de sexo masculino; edad promedio de los padres = 34.49, desviación típica = 6.20, el 59 % de sexo femenino). Se recopilaron datos sobre información demográfica, conductas de crianza y habilidades de regulación emocional de los niños mediante cuestionarios en línea al inicio del estudio y a los 12 meses posteriores. Los resultados de los análisis de ecuaciones estructurales longitudinales sugirieron que el afrontamiento por parte de los padres, medido al inicio del estudio, predijo la regulación emocional adaptativa y desadaptativa medida 12 meses después. Más específicamente, las sugerencias de afrontamiento del interés de los padres predijeron la regulación emocional adaptativa del niño, mientras que las sugerencias de afrontamiento del desinterés de los padres predijeron la regulación emocional desadaptativa del niño. Además, el género del niño surgió como moderador en la asociación longitudinal entre la socialización del afrontamiento del interés y la regulación emocional adaptativa del niño: si bien esta asociación fue pequeña y marginalmente significativa para las niñas, fue grande y estadísticamente significativa para los niños. Los resultados destacan la importancia de la socialización del afrontamiento por parte de los padres como posible favorecedora de las habilidades de regulación emocional de los niños de entre 5 y 12 años. Abstract : 本研究旨在验证以下假设, 即父母对孩童应对能力的培养(SOC)与孩子的情绪调节能力之间的关系是长期的。样本来自256位父母, 其孩子年龄在5至12岁之间(儿童平均年龄= 8.36, SD = 2.03, 男性54.7%;父母平均年龄= 34.49, SD = 6.20, 女性59%)。参与者被要求在起始阶段和12个月时填写在线问卷, 以供收集有关人口统计学信息, 育儿行为和儿童情绪调节能力方面的数据。纵向性的结构方程模型(SEM)分析的结果表明, 在基线测量的父母SOC预测了孩子12个月后测量到的在情绪调节方面的适应和调适不良的结果。更具体地说, 父母的积极培养孩子应对策略方面的建议预测了孩子情绪调节方面的适应性, 而父母缺乏对孩童应对能力的培养则预测了孩子在情绪调节方面的不良调适能力。此外, 在家长积极培养应对策略与儿童情绪调节适应性之间的纵向联系中, 儿童性别起了调节作用:尽管这种联系很小, 对女孩来说相对微小, 而对于男孩则较大, 并且具有统计学的显著意义。本项研究结果强调了家长的SOC的重要性, 因为它有可能提高5至12岁儿童的情绪调节能力。